2016
DOI: 10.21101/cejph.a4292
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Consumption and Academic Achievement: a Cross-sectional Study

Abstract: SUMMARYAim: Alcohol consumption among adolescents is a serious public health problem in South Korea. Our study examined the relationship between alcohol consumption and academic achievement in Korean adolescents. In 2011, 75,643 students from seventh to twelfth grade participated in the Seventh Korea Youth Risk Behaviour Web-based Survey (KYRBWS-VII)Method: We performed multivariate logistic regression analysis to examine the associations between alcohol consumption, frequency of severe alcohol intoxication, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Drinking is one of the most common problem behaviors. It is already well known that drinking in adolescence can negatively affect the individual’s physical and mental well-being and educational life [12]. The relationship between drinking and smoking in adolescents has been studied extensively [13]; however, to the best of our knowledge, there is still little research on the link between vaping and drinking among Korean adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Drinking is one of the most common problem behaviors. It is already well known that drinking in adolescence can negatively affect the individual’s physical and mental well-being and educational life [12]. The relationship between drinking and smoking in adolescents has been studied extensively [13]; however, to the best of our knowledge, there is still little research on the link between vaping and drinking among Korean adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that half of the Korean adolescents (42.3%) had the experience of alcohol consumption in 2018 [19]. Alcohol drinking can give a negative health impact such as cancer, hypertension, coronary heart disease, injuries, and the difficulty of academic achievement [20, 21]. Moreover, the prevalence of binge drinking among adolescents who drink alcohol has increased from 44.6% in 2008 to 52.5% in 2018 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, cognitive strategies for study were the highest contributor to the final solution, and the age of entry into elementary education had the least impact. As for the strategies, higher stud included s comprised goal-orien experience (Hill & Mrug, 2015;Sung et al, 2016), and considered these substances harmful to health. In addition, their attitude toward personal healthcare and the environment is positive, which leads to a healthy diet and more regular exercise (Pellicer et al, 2015).…”
Section: Resultsmentioning
confidence: 99%